Núcleo homeopático homeopatila 100® no cultivo de tilápias do Nilo (Oreochromis niloticus) em tanques-rede - Nervis, Juliana Alice Lösch (2016)
The aim of this study was to evaluate the effect of the product Homeopatila 100® on growth performance, hematological response, parasites prevalence, and hepatic and branchial histology of Nile tilapia (Oreochromis niloticus) cultured in cages. The experiment took 91 days. 1240 juvenile Nile tilapia (50.15±8.52 g) were used, distributed in 10 cages of 1.2m³, and fed with commercial extruded feed. The treatments consisted of a control treatment with 40 mL of Homeopatila 100®/kg of feed, and a control treatment without inclusion of the homeopathic product. A significant difference was observed only in the prevalence of ectoparasites, presenting a decrease over time for both treatments, and in hepatic histological evaluations, in which the treatment with homeopathic product presented a higher number of hepatocytes and a higher concentration of hepatic glycogen, whereas no difference was found between treatments for liver somatic index. Therefore, we concluded that the homeopathic complex Homeopatila 100® at a concentration of 40 mL/kg of feed presented significant results in hepatic histology, with a higher number of hepatocytes and a higher concentration of glycogen per area, not interfering on the growth performance, hematology, prevalence of parasites and branchial histology of Nile tilapia farmed in cages.